2020
DOI: 10.1007/s10340-020-01305-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable management of the vine mealybug in organic vineyards

Abstract: The vine mealybug (VMB), Planococcus ficus, is a major grapevine pest worldwide, whose chemical control is often unsatisfactory due to its cryptic behavior, insecticide resistance and high fecundity rate. Recently, increasing restrictions have been applied to insecticides used for managing VMB. This review discusses sustainable VMB management strategies in organic viticulture. Pheromone-mediated mating disruption has been proved to be effective in both organic wine and table-grape vineyards. Biocontrol project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 177 publications
(223 reference statements)
0
34
0
Order By: Relevance
“…Overall, the lower survival and fecundity of mealybugs developed on unfertilized grapevines may be due to nutritional limitations and/or lower nutritional value of phloem sap [57,58]. Soil management with cover crop species that participate in the N fixation process in the soil, e.g., legumes, can replace N fertilization and promote development and survival of the VMB [34]. Moreover, floor vegetation promotes the establishment of ants, which protect mealybugs from natural enemies, thereby favoring the pest infestation [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the lower survival and fecundity of mealybugs developed on unfertilized grapevines may be due to nutritional limitations and/or lower nutritional value of phloem sap [57,58]. Soil management with cover crop species that participate in the N fixation process in the soil, e.g., legumes, can replace N fertilization and promote development and survival of the VMB [34]. Moreover, floor vegetation promotes the establishment of ants, which protect mealybugs from natural enemies, thereby favoring the pest infestation [59].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, removal of bunch-zone leaves prevented economic damage by the European grapevine moth and grey mold [31], whereas water provision promoted the development of grapevine leafhoppers [32]. The wide literature on this subject highlights that cultural practices, including fertilization, should be included as sustainable control techniques within a multi-disciplinary approach to grape pest control [33,34]. Although such practices may not be effective as stand-alone control tactics, they can be suitably included in integrated pest control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the displays composing the host-seeking and parasitization behavior of A. vladimiri on P. comstocki were walking and drumming activity, arrestment close to the host, antennal tapping, probing, oviposition, and host dragging. In addition, a peculiar host defensive behavior was noted, i.e., a fast abdominal rocking movement against the parasitoid (kicking), coupled or not with the production of a viscous secretion against the parasitoid to impair its wings [23,24]. Host feeding behavior was not observed.…”
Section: No-choice Testsmentioning
confidence: 99%
“…Nevertheless, the mealybug habit of staying in concealed plant parts and the waxy cover of these insects make chemical control in some conditions poorly effective [4]. New tactics, alternative to chemicals, show a potential to reduce and suppress mealybug infestations, including biological control [5]. Previous studies showed the potential of natural enemies, such as Anagyrus vladimiri Triapitsyn [3] and Cryptolaemus montrouzieri Mulsant, in controlling these detrimental pests [6,7].…”
Section: Introductionmentioning
confidence: 99%